Metformin, Oxidative Stress and Male Infertility: Way Forward - Alam , Faiza; Nida Farooqui; Rehana Rehman (Journal of the Pakistan Medical Association, 2021)
Madam, There is an increased prevalence of infertility in male population. With reference to a variety of mechanisms, oxidative stress (OS) is responsible for alteration in structural and functional integrity of sperm leading to altered sperm parameters, hence leading to infertility (1). Metformin though proved to be a first-line hypoglycemic agent has demonstrated antioxidant properties in numerous tissues. It inhibits the mitochondrial respiratory chain in the liver, which leads to stimulation of AMP-activated protein kinase (AMPK)-dependent as well as AMPK-independent mechanisms (2). Metformin triggers alanine production within the Sertoli cells (SCs,) balances the NADH/NAD+ equilibrium and provides antioxidant environment. This drug is a treatment of choice in treating females with Polycystic Ovaries (PCOS) on the basis of its capability to reduce insulin sensitivity as well as angiogenesis through the nuclear factor ?B (NF-?B) pathway which renders it to reduce oxidant species, thus improving the reproductive environment (3). Continuous....